System Of Youth And Children’s Football In Uzbekistan: Historical Experience, Current Problems And Development Prospects (Texas Journal of Philology, Culture and History, 2026)
This article examines the system of youth and children’s football in Uzbekistan, focusing on its historical development, current challenges, and future prospects. The study analyzes the role of sports schools, football academies, infrastructure, and state support in improving young players’ training. Particular attention is given to regional disparities, shortage of qualified coaches, and organizational issues within the football system. The article also highlights international experience and proposes practical recommendations for strengthening youth football and increasing Uzbekistan’s competitiveness in world football